2014
DOI: 10.1556/comec.15.2014.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Gastropod communities in alpine grasslands are characterized by high beta diversity

Abstract: Alpine grasslands harbour species-rich communities of plants and invertebrates. We examined how environmental variables and anthropogenic impact shape species richness and community structure of terrestrial gastropods in alpine grasslands in the Val Müstair (Eastern Alps, Switzerland). Gastropods were sampled using a standardised method at 76 sites spanning an elevation range from 1430 m to 2770 m. A total of 4763 specimens representing 52 species were recorded. Correspondence analysis based on presence/absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Even if knowledge is still too scarce to conclude undoubtedly, only the smallest species seem able to survive extreme cold temperatures during winter. This hypothesis is supported by several studies offering evidence that land snail communities are less diverse at high altitudes and latitudes, where small taxa become more frequent ( Hausdorf and Hennig, 2003 ; Nekola et al ., 2013 ; Baur et al ., 2014 ; Horsák and Chytry, 2014 ; Schmera and Baur, 2014 ; Forsyth and Oldham, 2016 ). With climate warming, we would expect the gastropod community to become richer in bigger species, with consequences for competition, trophic webs, vegetation grazing and soil dynamics.…”
Section: Winter Temperature and Snow Covermentioning
confidence: 99%
“…Even if knowledge is still too scarce to conclude undoubtedly, only the smallest species seem able to survive extreme cold temperatures during winter. This hypothesis is supported by several studies offering evidence that land snail communities are less diverse at high altitudes and latitudes, where small taxa become more frequent ( Hausdorf and Hennig, 2003 ; Nekola et al ., 2013 ; Baur et al ., 2014 ; Horsák and Chytry, 2014 ; Schmera and Baur, 2014 ; Forsyth and Oldham, 2016 ). With climate warming, we would expect the gastropod community to become richer in bigger species, with consequences for competition, trophic webs, vegetation grazing and soil dynamics.…”
Section: Winter Temperature and Snow Covermentioning
confidence: 99%
“…Unfortunately, we did not have herbivory or distribution data for mollusks in our study areas. Studies conducted at other sites have found that gastropod diversity generally decreased with increasing elevation (e.g., Liew et al, 2010;Baur et al, 2014;Schmera and Baur, 2014). If such pattern is true for the Hengduan Mountains region, higher proportion of species with glandular trichomes at higher elevations is unlikely to relate to herbivory pressure from mollusks in our study area.…”
Section: Discussionmentioning
confidence: 52%
“…Although higher species richness at lower elevations is not surprising (Baur et al. , Schmera and Baur ), we must interpret this result with some caution. We generally surveyed lower elevation sites earlier in the season as snowpack prevented access to higher elevation sites until late season hotter and drier weather prevailed.…”
Section: Discussionmentioning
confidence: 71%